Hydrological Analysis for Flood Forecasting at Sg Golok River Basin Malaysia - Sidek L.M.; Basri H.; Yalit M.R.; bin Hassan M.H.; binti Mat Daud S.A.; Sekaran T.A./L. (Springer Science and Business Media Deutschland GmbH, 2023)
Disaster prevention; Disasters; Flood control; Watersheds; Weather forecasting; Extreme flood; Flood forecasting; Flood warning; Heavy rainfall; Hydrological analysis; Malaysia; National flood forecasting and warning system; River basins; Sg golok; Floods